The effects of service quality, perceived value and trust in home delivery service personnel on customer satisfaction: Evidence from a developing country. (November 2021) - Uzir, Md. Uzir Hossain; Al Halbusi, Hussam; Thurasamy, Ramayah; Thiam Hock, Rodney Lim; Aljaberi, Musheer A.; Hasan, Najmul; Hamid, Mahmud
Abstract: The rapid growth of online purchasing in recent years has emphasized the accompanying role of home delivery service provided by delivery personnel in ensuring customer satisfaction. On-time delivery, better service, generating positive customer perceived value, and trust towards service providers are influential factors that contribute to customer satisfaction. The aim of the study was to investigate the effects of service quality of home delivery personnel and perceived value on customer satisfaction, with trust playing an intervening role. It was conducted in Dhaka, Bangladesh, a less developed country with a new but rapidly growing digital sector. Data was collected from 259 respondents who received home delivery service, using a structured questionnaire. The conceptual model was analysed using partial least square structural equation modelling (PLS-SEM) with SmartPLS tool. The findings revealed that service quality, customer perceived value, and trust influenced customer satisfaction. The relationship between service quality and customer satisfaction and the relationship between customer perceived value and satisfaction were both partially mediated by trust. The findings contribute to the development and validation of a trust-based satisfaction model by extending the SERVQUAL model to incorporate perceived value in the presence of trust, while complying with expectation disconfirmation theory This study provides insights for managers to develop reliability and build trust in their service delivery personnel.